(untitled) (Journal of the College of Basic Education, 2026)
This research examines the transformations of center and margin in theatrical performance as one of the intellectual and aesthetic approaches that has contributed to reconsidering the concepts of dominance and marginalization at the heart of the per formative act of theatrical characters. The research aims to reveal the nature of the dialectical relationship between the duality of center and margin and their transformations in the actor’s performance within a theatrical production, highlighting the role of conflict and integration between them in producing a distinct theatrical performance on both technical and aesthetic levels. The research adopted a descriptive-analytical approach, using the play "The Wall" as a model of analysis. A number of character performances were studied and analyzed to reveal the mechanisms of center and periphery in vocal, physical, gestural, and rhythmic performance. The research concluded that the transformations of center and margin represent an effective analytical approach in understanding and deciphering the codes of theatrical performance. The nature of the relationship between them is not one of subordinate and dominant, but rather one of differing and conflicting roles that leads to their integration in order to produce an artistic, technical, and aesthetically pleasing theatrical performance.